Vitamin D Combined with Resveratrol Prevents Cognitive Decline in SAMP8 Mice - Cheng, Jinbo; Rui, Yehua; Qin, Liqiang; Xu, Jiaying; Han, Shufen; Yuan, Linxi; Yin, Xuebin; Wan, Zhongxiao (Current Alzheimer Research, 2017)
Background: Vitamin D (VD) and resveratrol (RSV) are two nutritional molecules that have reported neuroprotective effects, and findings from cellular models suggest that resveratrol could potentiate vitamin D's effects. The senescence-accelerated mouse-prone 8 (SAMP8) is a useful model of Alzheimer's disease (AD)-related memory impairment. Objective: We aimed to explore how the combination of vitamin D with resveratrol would affect memory impairments shown by SAMP8 mice, as well as the potential mechanisms. Method: SAMP8 mice and their control senescence-accelerated mouse resistant 1 (SAMR1) mice (10 weeks old) were divided into 5 groups, i.e. SAMR1 group, SAMP8 group, SAMP8 mice supplemented with VD group, SAMP8 mice supplemented with RSV group and SAMP8 mice supplemented with both VD and RSV group. At the end of the intervention, Morris water maze (MWM) test was used to assess cognitive function. Hippocampus and parietal cortex were dissected for further analysis. Results: The combination of VD and RSV significantly increased time spent in target quadrant and the number of crossing via MWM test. In hippocampus, the combined intervention significantly reduced soluble Aβ42 level and BACE1 protein expression. In cortex, the combined treatment significantly reduced phosphorylation of tau at serine404 and p-p53, as well as enhanced p-CREB protein expression. The combination also significantly reduced GFAP and p-NFΚB p65 in both hippocampus and cortex. Conclusion: The combined intervention might exert greater neuroprotective effects in SAMP8 mice, this might be associated with the fact that the combined intervention could positively affect amyloidogenic pathways, neuroinflammation, tau phosphorylation and probably apoptosis markers.
Keywords: endoplasmic reticulum stress